Sequential vs. Single-Round Uniform-Price Auctions - Claudio Mezzetti; Aleksandar Pekec; Ilia Tsetlin (Fondazione Eni Enrico Mattei (FEEM), 2004)
We study sequential and single-round uniform-price auctions with affiliated values. We derive symmetric equilibrium for the auction in which k1 objects are sold in the first round and k2 in the second round, with and without revelation of the first-round winning bids. We demonstrate that auctioning objects in sequence generates a lowballing effect that reduces first-round revenue. Thus, revenue is greater in a single-round, uniform auction for k = k1 + k2 objects than in a sequential uniform auction with no bid announcement. When the first-round winning bids are announced, we also identify two informational effects: a positive effect on second-round price and an ambiguous effect on first-round price. The expected first-round price can be greater or smaller than with no bid announcement, and greater or smaller than the expected price in a single-round uniform auction. As a result, total expected revenue in a sequential uniform auction with winning-bids announcement can be greater or smaller than in a single-round uniform auction.
Keywords: D44; D42; 330; Multi-unit auctions; Sequential auctions; Uniform-price auction; Affiliated values; Information revelation; Auktionstheorie; Theorie